Ekonomi Tumbuh, Stunting Turun: Budikdamber sebagai Gerakan Kemandirian Kader PKK Mandalamekar - Perdana Wahyu Santosa; Elita Donanti; Harry Budiantoro; Adinda Primadini; Firra Nurisma (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
This Community Service Program (PKM) aims to empower PKK and Posyandu cadres in Mandalamekar Village through the development of creative economy activities based on Budikdamber (fish farming in buckets). This method was chosen because it is practical, space-saving, and economical, while also providing opportunities to increase household income and supply protein sources for toddlers and pregnant women through the Supplementary Feeding Program (PMT) as an effort to reduce stunting rates. The program was carried out on Friday, August 3, 2024, at the Mandalamekar Village Hall, involving PKK and Posyandu cadres, village officials, and local residents. The activities included technical training on catfish farming, nutrition education, and assistance in processing fish products into value-added items such as nuggets and shredded catfish (abon). The program’s success indicators include active participation of participants, the adoption of Budikdamber practices at the household level, improved nutritional knowledge, and the utilization of harvests for PMT at the Posyandu. In the long term, this program is expected to foster an independent community based on creative economic activities that support family welfare improvement and sustainable stunting reduction, thereby serving as a model for integrated village empowerment combining both health and economic aspects.